The Semiotics of Fear and Anxiety in Andalusian Petitionary Poetry of the Taifa Kings Era (422–484 AH) - Abbas, Muhammad Attar Zughair; Abdul-Hussein, Sadiq Jafar (Journal of Cultural Analysis and Social Change, 2025)
This study seeks to explore the passions and underlying emotions in Andalusian petitionary poetry during the Taifa Kings era, analyzing selected examples through the lens of semiotics of desires (simiā’ al-ahwā’). It examines the linguistic devices employed by the poetic self and their procedural representations to identify the internal semiotic markers of the human psyche, given that the poetic discourse of this period is saturated with emotional centers that govern the production of meaning. Among these emotions, fear and anxiety emerge prominently, reflecting the volatile political, social, and intellectual context of the Taifa period. This type of emotional expression constitutes a crucial component of petitionary poetry, as poets often reveal a state of anxiety that could endanger their lives if they fail to appeal successfully to authority, lose their beloved, or exacerbate paternal anger. The addressed authority in this poetic context typically involves one of three figures: the ruler, the beloved, or the father.